Identification of lignans as major components in the phenolic fraction of olive oil - Owen, Robert; Mier, Walter; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut (Clinical chemistry, 2000)
Abstract. Background: Because olive oil is an important component of the Mediterranean diet, it is necessary to establish unequivocal identification of the major potential antioxidant phenolic compounds it contains.